2010
DOI: 10.4103/0970-4388.66741
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of oral health promoting factors among caretakers of children attending day-care centers in Kubang Kerian, Malaysia: A preliminary study

Abstract: Implementation of nursery-based oral health promotion programs for secondary caretakers is needed to counteract early childhood caries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 20 publications
6
42
1
Order By: Relevance
“…Only twelve percent of the surveyed population knew that ECC is actually an infectious disease, which could be transmitted via cavity-causing bacteria from caregivers to children. These results are similar to that of Mani et al who noted that only 15% of the surveyed participants were familiar with the role of bacteria in caries etiology (19); the other studies found somewhat higher percentages: from 33% to 46% (19,35). It is obvious that concepts of vertical and horizontal bacterial transmission are not properly addressed within formal education about oral health.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Only twelve percent of the surveyed population knew that ECC is actually an infectious disease, which could be transmitted via cavity-causing bacteria from caregivers to children. These results are similar to that of Mani et al who noted that only 15% of the surveyed participants were familiar with the role of bacteria in caries etiology (19); the other studies found somewhat higher percentages: from 33% to 46% (19,35). It is obvious that concepts of vertical and horizontal bacterial transmission are not properly addressed within formal education about oral health.…”
Section: Discussionsupporting
confidence: 74%
“…These factors have been identified in numerous studies as very influential to caries risk and severity of the disease; unfortunately, the level of mothers's knowledge about them was frequently low (they were not aware of the hidden sugars in breast milk) (19,35,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study about 39.8% of parents started semisolid food at the age of 6-9 months whereas only 11.8% of parents started semisolid food by the age of 1 yr. Where as in a study conducted by Mani (Mani SA et al .2010) et al in (2010) in Malaysia about 64.7 % of parents started the semisolid food only by the age of 1 year which is comparatively higher than this study. The early age of introduction of semisolid food increases the rate of prevalence of ECC, so the parents should be instructed to strictly follow the oral hygiene practices.…”
Section: Discussioncontrasting
confidence: 43%
“…In another study conducted by Orawan et al in (Suwansingha O et al2014) Thailand the prevalence was 46.3% which was higher than our study. Similarly in a study conducted by Mani (Mani SA et al .2010) et al in 2010 in Malaysia it was revealed that about 42% of parents gave plane water after each feeding. Most of the parents were not aware of importance of feeding with water after feeding milk as the remnants from milk present on the tooth surface can cause demineralisation of the enamel, which later leads to frank cavitation.…”
Section: Methodsmentioning
confidence: 99%